The Laplace inverse of L^{-1}left[frac{s}{s^2+5^2}right] is a) cos(5t) b) sin h(5t) c) sin(5t) d) cos h(5t)

Laplace transform
asked 2020-12-30
The Laplace inverse of \(L^{-1}\left[\frac{s}{s^2+5^2}\right]\) is
\(a) \cos(5t)\)
\(b) \sin h(5t)\)
\(c) \sin(5t)\)
\(d) \cos h(5t)\)

Answers (1)

Step 1
To find the Laplace transformation of \(L^{-1}\left[\frac{s}{s^2+5^2}\right]\)
let \(\varphi(s)\) be the function whose Laplace transformation will be \(\frac{s}{s^2+5^2}\)
Applying inverse we get,
\(\varphi(s)=L^{-1}\left[\frac{s}{s^2+5^2}\right] \dots(1)\)
Step 2
since, we know that
\(L(\cos as)=\frac{s}{s^2+a^2}\)
\(\text{and } (\cos as)=L^{-1}\left(\frac{s}{s^2+a^2}\right)\)
From equation (1),
Hence, the inverse Laplace for given expression is cos5t.
Best answer

expert advice

Need a better answer?

Relevant Questions

asked 2021-06-06
Use the table of Laplace transform and properties to obtain the Laplace transform of the following functions. Specify which transform pair or property is used and write in the simplest form.
a) \(x(t)=\cos(3t)\)
b)\(y(t)=t \cos(3t)\)
c) \(z(t)=e^{-2t}\left[t \cos (3t)\right]\)
d) \(x(t)=3 \cos(2t)+5 \sin(8t)\)
e) \(y(t)=t^3+3t^2\)
f) \(z(t)=t^4e^{-2t}\)
asked 2021-05-12
One property of Laplace transform can be expressed in terms of the inverse Laplace transform as \(L^{-1}\left\{\frac{d^nF}{ds^n}\right\}(t)=(-t)^n f(t)\) where \(f=L^{-1}\left\{F\right\}\). Use this equation to compute \(L^{-1}\left\{F\right\}\)
\(F(s)=\arctan \frac{23}{s}\)
asked 2021-02-25
Use properties of the Laplace transform to answer the following
(a) If \(f(t)=(t+5)^2+t^2e^{5t}\), find the Laplace transform,\(L[f(t)] = F(s)\).
(b) If \(f(t) = 2e^{-t}\cos(3t+\frac{\pi}{4})\), find the Laplace transform, \(L[f(t)] = F(s)\). HINT:
\(\cos(\alpha + \beta) = \cos(\alpha)\cos(\beta) - \sin(\alpha) \sin(\beta)\)
(c) If \(F(s) = \frac{7s^2-37s+64}{s(s^2-8s+16)}\) find the inverse Laplace transform, \(L^{-1}|F(s)| = f(t)\)
(d) If \(F(s) = e^{-7s}(\frac{1}{s}+\frac{s}{s^2+1})\) , find the inverse Laplace transform, \(L^{-1}[F(s)] = f(t)\)
asked 2020-10-25
Please provide steps
The inverse Laplace transform for
\(\displaystyle{F}{\left({s}\right)}=\frac{8}{{{s}+{9}}}-\frac{6}{{{s}^{2}-\sqrt{{3}}}}\) is
a) \(\displaystyle{8}{e}^{{-{9}{t}}}-{6} \sin{{h}}{{\left({3}{t}\right)}}\)
b) \(\displaystyle{8}{e}^{{-{9}{t}}}-{6} \cos{{h}}{\left({3}{t}\right)}\)
c) \(\displaystyle{8}{e}^{{{9}{t}}}-{6} \sin{{h}}{\left({3}{t}\right)}\)
d) \(\displaystyle{8}{e}^{{{9}{t}}}-{6} \cos{{h}}{\left({3}{t}\right)}\)